Fecal Calprotectin as a Marker of the Gut Immune System Activation Is Elevated in Parkinson’s Disease - Mulak, Agata; Koszewicz, Magdalena; Panek-Jeziorna, Magdalena; Koziorowska-Gawron, Ewa; Budrewicz, Sławomir (Frontiers in Neuroscience, 2019)
Introduction: Alpha-synucleinopathy constituting a characteristic feature of Parkinson’s disease (PD) occurs at all levels of the brain-gut axis including the enteric nervous system (ENS). Lesions in the ENS may be connected with gut inflammation, increased intestinal permeability and dysmotility contributing to the pathogenesis of PD and its gastrointestinal manifestations. Aims: to evaluate fecal calprotectin and zonulin as biomarkers of gut inflammation and intestinal barrier dysfunction in PD patients. Methods: Quantitative evaluation of fecal biomarkers was performed by ELISA tests in 35 PD patients and 20 healthy controls. Additionally, patients filled out a short questionnaire concerning gastrointestinal symptoms. Results: Median fecal calprotectin level (μg/g) was significantly higher in PD patients compared to the controls: 54.5[29.0-137.9] vs 9.7 [5.2-23.3], p<0.0001. Applying age-related reference ranges, the increased fecal calprotectin level was found in 43% of PD patients and in none of the control subjects (p<0.001). No correlation between fecal calprotectin level and PD duration was observed. No statistically significant difference between the groups regarding zonulin level was found. The most frequent bowel symptoms reported by PD patients included constipation (69% of subjects), feeling of incomplete evacuation (51%), bloating (51%), abdominal pain (20%), and alternating bowel movement pattern (17%). Conclusion: The evaluation of fecal calprotectin level may be a useful tool to detect the signs of gut immune system activation present in a remarkable number of PD patients, also in the early stage of the disease.Calprotectinmay constitute a critical link between amyloid formation and neuroinflammatory cascades serving as a prospective diagnostic and therapeutic target.